2021
DOI: 10.1002/jee.20380
|View full text |Cite
|
Sign up to set email alerts
|

The role of college knowledge and proactive behavior on participation in cocurricular activities

Abstract: Background Demographic characteristics are known to influence participation in cocurricular activities. Less studied are the effects of other background characteristics. Purpose We hypothesize that considering college knowledge and students' proactive behaviors in tandem with demographics provides better models for predicting such participation. Method We developed a questionnaire and administered it to 3,618 domestic third‐ and fourth‐year undergraduate engineering students at a large public R1 Midwestern uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Of the articles that listed participation requirements for high school seniors and undergraduate participants, most required students to have a particular academic standing to receive or maintain program support (Anderson-Rowland & Ruben, 2008;Hrabowski & Maton, 1995;Kendricks & Arment, 2011;Maton et al, 2000). Contrarily, middle school and high school programs allowed students to participate as long as they had an interest (Di Salvo et al, 2013;Ferreira, 2002) or qualified as low socioeconomic status (SES; Dunn & Veltman, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Of the articles that listed participation requirements for high school seniors and undergraduate participants, most required students to have a particular academic standing to receive or maintain program support (Anderson-Rowland & Ruben, 2008;Hrabowski & Maton, 1995;Kendricks & Arment, 2011;Maton et al, 2000). Contrarily, middle school and high school programs allowed students to participate as long as they had an interest (Di Salvo et al, 2013;Ferreira, 2002) or qualified as low socioeconomic status (SES; Dunn & Veltman, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The explanation of concepts should not be done randomly. This practice is common and usual [ 43 ], but it must be complemented with an adequate hierarchization, so that the teacher should identify which are the key or the most important concepts of each topic that is addressed. It has been shown that this practice facilitates adequate organization of student learning, which leads to better overall learning on the course [ 44 ].…”
Section: Overall Discussionmentioning
confidence: 99%
“…The notion of proactiveness in engineering students, characterised by the introduction of new products and services ahead of competitors and anticipation of future demand to seize opportunities (Rauch et al, 2009), is subject to diverse influences. Millunchick et al (2021) emphasise the role of individuals or institutions in shaping proactive behaviour, while Henderson et al (2018) argue that pre-college characteristics and experiences predict such behaviour among engineering students. Nagahi et al (2020) observe a positive relationship between proactive character and the ability of engineering students to adapt to change and uncertainty.…”
Section: Proactivenessmentioning
confidence: 99%